PERANAN Hj. ROSLAINI SEBAGAI TOKOH PEMBERDAYA PEREMPUAN RIAU TAHUN 1970-2018 - Hartanti, Intan Dwi; Ibrahim, Bedriati; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: In the traditional view, women are identical as weak, delicate and emotional. Along with the emancipation movement more and more women can appear at the forefront as leaders who were previously dominated by men. Many efforts have been made by Riau women leaders to promote their fellow human beings. One of them is Hj. Roslaini who seeks to advance women through various women's organizations in Riau. The purpose of this study is 1) to find out the life history of Hj. Roslaini, 2) to find out the role of Hj. Roslaini in empowering woman at Riau, 3) to find out the challenges faced by Hj. Roslaini in empowering women at Riau, 4) to find out the existence of Hj. Roslaini at empowering woman right now. The research uses the historical method and data obtained from the interviews plus data obtained from books and archives. The results of this study Hj. Roslaini was born on September 27, 1938 in Pasir Pengaraian from the couple Djadin bin Pinang and Baiyah binti M. Karim. Hj. Roslaini became active in women's organizations in 1970, through these organizations Hj. Roslaini seeks to empower women. The organization that had been followed by Hj. Roslaini is PERTIWI, Dharma Wanita, PKK, BKOW, BKKKS, BKMT, Pusdatin Puanri and PRBF. In an effort to empower women Hj. Roslaini has the challenge of managing members of her organization, lack of understanding and concern for women in education and health, lack of women's self-confidence and people's perspectives on abilities. Now in his old age Hj. Roslaini still serves as chair of the PRBF and advisor to women's organizations.Key Words: Hj. Roslaini, Riau Women's Empowerment, Role